Spontaneous and induced abortion trends and determinants in the Northeast semiarid region of Brazil: a transversal series - Luciano Lima Correia; Hermano Alexandre Lima Rocha; Álvaro Jorge Madeiro Leite; Jocileide Sales Campos; Anamaria Cavalcante e Silva; Márcia Maria Tavares Machado; Sabrina Gabriele Maia Oliveira Rocha; Thales Nogueira Gomes; Antônio José Ledo Alves da Cunha
Abstract Objectives: this study intends to estimate the rates, associated factors and trends of selfreported abortion rates in the northeast of Brazil. Methods: series of population-based surveys realized in Ceará, northeast of Brazil, one of the poorest states in the country. A sample of about 27,000 women of reproductive age was used. Abortion was assessed according to women´s information and rates were calculated using official population estimates. The trends and the association among socioeconomic and reproductive factors were studied using regressive models. Results: a trend for reduction in rates was identified. For induced abortion, the determinants were: not having a partner, condom in the last sexual intercourse, first child up to 25years old (AOR= 5.21; ACI: 2.9 - 9.34) and having less than 13years old at first sexual intercourse (AOR= 5.88; ACI: 3.29 - 10.51). For spontaneous abortion were: having studied less than 8 years, knowledge and use of morning-after pill (AOR= 26.44; ACI: 17.9 - 39.05) and not having any children (AOR= 3.43). Conclusions: rates may have been low due to self-reporting. Young age and knowledge about contraceptive methods were associated to both kinds of abortion, while education level along with spontaneous and marital status with induced. Programs to reduce abortion rates should focus on single younger women with low education.